Aligning use of intensive care with patient values in the USA: past, present, and future - Turnbull, Alison E (Lancet Respir Med, 2019)
For more than three decades, both medical professionals and the public have worried that many patients receive non-beneficial care in US intensive care units during their final months of life. Some of these patients wish to avoid severe cognitive and physical impairments, and protracted deaths in the hospital setting. Recognising when intensive care will not restore a person’s health, and helping patients and families embrace goals related to symptom relief, interpersonal connection, or spiritual fulfilment are central challenges of critical care practice in the USA. We review trials from the past decade of interventions designed to address these challenges, and present reasons why evaluating, comparing, and implementing these interventions have been difficult. Careful scrutiny of the design and interpretation of past trials can show why improving goal concordant care has been so elusive, and suggest new directions for the next generation of research.